Pre-entry perceptions of students entering five health professions: implications for interprofessional education and collaboration. Issue 1 (2nd January 2021) - Price, Sheri L.; Sim, Meaghan; Little, Victoria; Almost, Joan; Andrews, Cynthia; Davies, Harriet; Harman, Katherine; Khalili, Hossein; Reeves, Scott; Sutton, Evelyn; LeBrun, Jeffery
ABSTRACT: Dysfunctional interprofessional teams are a threat to health system performance and the delivery of quality patient outcomes. Implementing strategies that prepare future health professionals to be effective collaborators requires a comprehensive understanding of how early professional socialization and professional identity formation occur. We present findings from a qualitative study, grounded in narrative methodology, examining early professional socialization among students across five health professional programs (dentistry, medicine, nursing, pharmacy, physiotherapy) in the first year of health professional training. Between April and September 2015, students (n = 49) entering programs at an Atlantic Canadian University participated in one-on-one, audiotaped interviews starting before formal program orientation. Pre-entry interviews focused on factors influencing students' career choice and expectations of future profession and interprofessional collaboration (IPC). Findings revealed that many different experiences influenced participants' career choice and framed the social positioning of their future career (e.g., leadership, prestige, autonomy). Participant narratives revealed the existence of stereotypes pertaining to their chosen and other health professions. Study findings provided insights that may help strengthen initiatives to promote positive professional identity formation within the context of IPC. Implications of this research highlight the need for the early introduction of IPC including pre-entry recruitment messaging for prospective health professionals.